VR Serious Game for Myoelectric Prosthesis Training with Tactile Feedback - Cavalcante, Reidner Santos; Gaballa, Aya; Cabibihan, John-John; Soares, Alcimar; Lamounier, Edgard (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais Estendidos do XXIV Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2022.227938, 2022)
In recent years, Virtual Reality (VR) applications have attracted increasing attention for preparing amputees to properly use a prosthesis. In this paper, we propose an SG-based system that uses immersive Virtual Reality (iVR) and EMG signal processing to provide a training environment for amputees who are supposed to use myoelectric prostheses. This type of prosthesis requires a more complex control system. The system described in this paper runs on a Vive Pro System using a Vive Tracker to track the user's arm position and orientation and mirror the movement into a virtual prosthesis. EMG signals control the opening and closing of the virtual prosthesis, and vibrational elements placed on the user's forearm provide sensory feedback. The proposed system acts as a useful therapeutic tool for amputee rehabilitation. Our results show that virtual training can be greatly improved when proper tactile feedback is provided, especially for myoelectric controlled prostheses.